2006
DOI: 10.1007/s00384-005-0079-0
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of short-term outcomes after laparoscopic resection for rectal cancer

Abstract: LR is associated with less postoperative morbidity, but longer operation time. A prospective randomized controlled trial is warranted to fully investigate these and other outcome measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
56
1
9

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(68 citation statements)
references
References 15 publications
2
56
1
9
Order By: Relevance
“…We found that laparoscopic APR was associated with less intraoperative bleeding, shorter interval between operation and diet resumption and shorter hospital stay. Our results were not consistent with previous studies indicating that laparoscopic APR is associated with earlier postoperative recovery (20,21) and less postoperative morbidity (22). Oncologic outcome was reported to be comparable with open APR (16).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…We found that laparoscopic APR was associated with less intraoperative bleeding, shorter interval between operation and diet resumption and shorter hospital stay. Our results were not consistent with previous studies indicating that laparoscopic APR is associated with earlier postoperative recovery (20,21) and less postoperative morbidity (22). Oncologic outcome was reported to be comparable with open APR (16).…”
Section: Discussioncontrasting
confidence: 99%
“…Several studies compared long-term outcomes of patients with low rectal cancer between laparoscopic and open procedures. Almost all these studies demonstrated that long-term oncologic outcome of laparoscopic approach is comparable with open APR (10)(11)(12)(13)(14)(15)(16)(20)(21)(22). The problem for addressing this issue is relative rarity of the procedure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gao and coworkers 93 analyzed 11 studies in the literature from 1995 to 2005, which included 285 patients who had undergone LARR. The study found laparoscopic surgery to be associated with lower morbidity rates but longer operative times.…”
Section: Laparoscopic Resection For Rectal Cancermentioning
confidence: 99%
“…The laparoscope seems to facilitate pelvic dissection including identification and preservation of critical structures such as the autonomic nervous system [11][12] . Laparoscopic TME for rectal cancer is feasible and safe; the short-, mid-and long-term outcomes of the operation are favorable compared with those of conventional open surgery [13][14][15][16][17] . However, the laparoscopic TME for rectal cancer is complicated and has some technical difficulties during operation; surgeons had to invent some methods to resolve the problem [18][19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%